Role of sympathetic pathway in light-phase time-restricted feeding-induced blood pressure circadian rhythm alteration - Hou, Tianfei; Chacon, Aaron N.; Su, Wen; Katsumata, Yuriko; Guo, Zhenheng; Gong, Ming C. (Frontiers in Nutrition, 2022)
Disruption of blood pressure (BP) circadian rhythm, independent of hypertension, is emerging as an index for future target organ damage and is associated with a higher risk of cardiovascular events. Previous studies showed that changing food availability time alters BP rhythm in several mammalian species. However, the underlying mechanisms remain largely unknown. To address this, the current study specifically investigates 1) the relationship between rhythms of food intake and BP in wild-type mice; 2) effects of light-phase time-restricted feeding (TRF, food only available during light-phase) on BP circadian rhythm in wild-type and diabetic db/db mice; 3) the roles of the autonomic system and clock gene in light-phase TRF induced changes in BP circadian rhythm. Food intake and BP of C57BL/6J and db/db mice were simultaneously and continuously recorded using BioDAQ and telemetry systems under ad libitum or light-phase TRF. Per2 protein daily oscillation was recorded in vivo by IVIS spectrum in mPer2Luc mice. Autonomic nerve activity was evaluated by heart rate variability, baroreflex, urinary norepinephrine (NE) and epinephrine (Epi) excretion, and mRNA expressions of catecholamines biosynthetic and catabolic enzymes, and alpha-adrenergic receptors in mesenteric resistance arteries. We found that in wild-type mice, the BP level was correlated with the food intake temporally across the 24 hours. Reversing the feeding time by imposing light-phase TRF resulted in reverse or inverted BP dipping. Interestingly, the net changes in food intake were correlated with the net alteration in BP temporally under light-phase TRF. In db/db mice, light-phase TRF worsened the existing nondipping BP. The food intake and BP circadian rhythm changes were associated with alterations in Per2 protein daily oscillation and the time-of-day variations in heart rate variability, baroreflex, and urinary excretion of NE and Epi, and increased mRNA expression of Slc6a2 (encoding NE transporter) and Adra1d (encoding alpha-adrenergic receptor 1d) in the mesenteric resistance arteries, indicating the sympathetic nervous system (SNS) was modulated after light-phase TRF. Collectively, our results demonstrated that light-phase TRF results in reverse dipping of BP in wild-type and diabetic db/db mice and revealed the potential role of the sympathetic pathway in light-phase TRF-induced BP circadian rhythm alteration.